Testing Neurotransmitters for Toxicity with a Luminescent Biosensor: Implications for Microbial Endocrinology - Alexander V. Oleskin ,; Elena V. Sorokina ,; Alevtina P. Zarubina ,; Inna M. Parkhomenko, (Journal of Pharmacy and Nutrition Sciences, 2017)
Background: The human organism is a complex superorganism including numerous eukaryotic, eubacterial, and archaean cells. The qualitative and quantitative assessment of the microbiota toxicity of chemical agents, i.e., their inhibitory effects on the microbial inhabitants of the human organism in health and disease, seems to hold much value in this context. In this work, a bacterial luminescence-based express test system for microbiota toxicity is applied to neurotransmitters such as serotonin, dopamine, norepinephrine, and histamine. Methods: The biosensor was based on a GM Escherichia coli K12 strain (TGI) that contained the lux operon of the luminescent soil bacterium Photorhabdus luminescencens ZMI. The biosensor was exposed to the action of the tested neurotransmitters for 5 to 60 minutes The intensity of bacterial luminescence (counts.sec-1) was monitored in the control and the experimental samples with a Biotoks 6 ms luminometer (Russia); the toxicity index (T) of the neurotransmitters was determined. Results: A marked toxic effect on bioluminescence was produced by serotonin, histamine, and dopamine at concentrations exceeding 80 µg/ml, 100 µg/ml, and 1 mg/ml, respectively. At lower concentration, these neurotransmitters were “negatively toxic”, i.e. stimulatory in terms of the effect on bacterial luminescence. In contrast, norepinephrine inhibited luminescence at all concentrations tested. Conclusions: The bacterial luminescence-based testing method is applicable to the assessment of the destructive and stimulatory effects of neurotransmitters; the data obtained are of microbiological and clinical relevance.